The Principles of the Concept of Maslahah in Islamic Family Law of a Wife Looking for Living Husband Taking Care of Household Work - Firdaus, Firdaus; Mursal, Mursal; Desminar, Desminar; Halim, Syaflin (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to explore the implementation principles of the Maslahah concept in the context of Islamic Family Law, with a specific focus on the case study of a working wife and a husband responsible for household duties. Another purpose for knowing about the family harmonism. Apart from that, to understand that family harmony is when the family is managed by the husband or man. Researched using qualitative methods with a case study approach. The principles of maslahah use for this research about hifz al-mal, hifz al-nafs, hifz al-nasl, hifz al-‘aql, and hifz al-din. The data used is a total of 6 primary data and secondary data from various relevant research. The research instrument is validated through reference validation. Data analysis is carried out by presenting data, reducing data, interpreting data, and drawing conclusions. This research succeeded in finding the existence of maslahah principles that can look at the problem of wives working and husbands taking care of the house from several points of view. Meanwhile, each party's views can be answered through hifz al-mal, hifz al-nafs, hifz al-nasl, hifz al-'aql, and hifz al-din. The family wgom the wives go to work they are trustly always keep the harmonism family, because their reason about the economy.